Role of NADPH oxidase in host defense against aspergillosis - Grimm, Melissa J. (Med Mycol, 2010)
NADPH oxidase plays a critical role in antimicrobial host defense, as evident in chronic granulomatous disease (CGD), an inherited disorder of the NADPH oxidase characterized by severe bacterial and fungal diseases. Invasive aspergillosis and other moulds are the major cause of mortality in CGD. We also learn from CGD patients that NADPH oxidase plays an important role in regulating inflammation; CGD patients are prone to developing inflammatory diseases such as inflammatory bowel disease, obstructive granulomata of the genitourinary tract, and hypersensitivity pneumonitis. Indeed, the NADPH oxidase plays an essential role in calibrating innate and T-cell responses to control the growth of inhaled fungi while protecting against excessive and injurious inflammation. Knowledge gained on the mechanisms by which NADPH oxidase kills fungi and regulates inflammation may lead to new therapeutics for CGD and will have broad relevance to understanding host-pathogen interactions between mammals and ubiquitous moulds to which we are continually exposed.